(untitled) (Hematology Meeting Reports, 2009)
The pro-malignant role of thrombin in tumor adhesion, growth, metastasis and angiogenesis is well recognized.1-6 However, the mechanism of thrombin-induced angiogenesis is not clear. Vascular regulatory proteins and growth factors, particularly metalloproteinases (MMP-1, MMP-2, MMP-9), vascular endothelial growth factor (VEGF), angiopoietin-1 (Ang-1), and angiopoietin-2 (Ang-2), are required for the regulation of blood vessel formation. Thrombin-induced angiogenesis in a chick chorioallantoic membrane (CAM) assay is associated with upregulation of the major vascular endothelial growth factor (VEGF) as well as Angiopoietin-2 (Ang-2).6 Thrombin also upregulates VEGF and the major VEGF receptor KDR in endothelial cells and induces the secretion of VEGF and Ang-1 from platelets. Thrombin upregulates Ang-2, MMP-1 and MMP-2 in endothelial cells. However, the cellular mechanisms responsible for thrombin-induced upregulation of these genes have not been established.